FAPI PET/CT in the Diagnosis of Abdominal and Pelvic Tumors - Yang, Tianshuo; Ma, Long; Hou, Haodong; Gao, Feng; Tao, Weijing (Frontiers in Oncology, 2022)
Positron emission tomography/computed tomography (PET/CT) with 18F-fluorodeoxyglucose (18F-FDG) is currently a standard imaging examination used in clinical practice, and plays an essential role in preoperative systemic evaluation and tumor staging in patients with tumors. However, 18F-FDG PET/CT has certain limitations in imaging of some tumors, like gastric mucus adenocarcinoma, highly differentiated hepatocellular carcinoma, renal cell carcinoma, and peritoneal metastasis. Therefore, to search for new tumor diagnosis methods has always been an important topic in radiographic imaging research. Fibroblast activation protein (FAP) is highly expressed in many epithelial carcinomas, and various isotope-labelled fibroblast activation protein inhibitors (FAPI) show lower uptake in the brain and abdominal tissues than in tumor, thus achieving high image contrast and good tumor delineation. In addition to primary tumors, FAPI PET/CT is better than FDG PET/CT for detecting lymph nodes and metastases. Additionally, the highly selective tumor uptake of FAPI may open up new application areas for the non-invasive characterization, staging of tumors, as well as monitoring tumor treatment efficacy. This review focuses on the recent research progress of FAPI PET/CT in the application to abdominal and pelvic tumors, with the aim of providing new insights for diagnostic strategies for tumor patients, especially those with metastases.